Neutrophil Subsets in Periodontal Health and Disease: A Mini Review - Hirschfeld, Josefine (Frontiers in Immunology, 2020)
Neutrophils are amongst the most abundant immune cells within the periodontal tissues and oral cavity. As innate immune cells, they are first line defenders at the tooth-mucosa interface, and can perform an array of different functions. With regard to these, it has been observed over many years that neutrophils are highly heterogeneous in their behavior. Therefore, it has been speculated that neutrophils, similarly to other leukocytes, exist in distinct subsets. Several studies have investigated different markers of neutrophils in oral health and disease in recent years in order to define potential cell subsets and their specific tasks. This research was inspired by recent advancements in other fields of medicine in this field. The aim of this review is to give an overview of the current evidence regarding the existence and presence of neutrophil subsets and their possible functions, specifically in the context of periodontitis, gingivitis and periodontal health.